New Resistor-Less Electronically Tunable OTA-based Fully Floating FDNR Simulator - Bhardwaj, Kapil; Srivastava, Mayank; Tangsrirat, Worapong (My University, 2023)
A floating FDNR using four OTAs (operational transconductance amplifiers) and two grounded capacitances have been reported in this article. As per the reviewed literature, the proposed floating FDNR is based upon a minimum number of transistors with a resistor-less and grounded capacitances based structure as compared to any other FDNR simulators and can be considered the most compact configuration ever reported. It offers some excellent features like; electronically tunable behavior, purely resistor-less architecture, no restraint of parameter values matching, use of only grounded capacitances, and fully symmetric floating architecture. We have investigated the circuit for port parasitics and non-ideal gains of the employed OTAs and presented the analysis. It is found that the circuit nature remains almost unchanged in non-ideal conditions. The influence of frequency-dependent transconductance has also been analyzed. The FDNR simulation through the reported circuit has been verified through the PSPICE-generated simulation results. The higher-order CDR filtering circuit application of the proposed FDNR has also been reported and checked through simulations. The presented OTA-based FDNR has been experimentally verified through the CA3080 IC-based implementation and results are discussed.
Keywords: Electronic adjustability; Frequency-dependent negative resistance (FDNR); Operational transconductance amplifier (OTA)